The Triple Impact of Tourism: Economic Growth, Cultural Dynamics, and Environmental Change - Amin, Ahmad Faiz; Budilestari, Windiarti (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2025)
Tourism has emerged as one of the fastest-growing global sectors, offering substantial contributions to economic development, cultural preservation, and environmental awareness. However, its rapid expansion also presents significant challenges across these dimensions. This study employs a literature review approach to critically analyze the multidimensional impacts of tourism on economic, socio-cultural, and environmental sectors. Economically, tourism stimulates growth through employment generation, local income enhancement, and foreign exchange earnings. Nonetheless, it may also lead to economic leakage, income inequality, and overdependence on seasonal demand. From a socio-cultural perspective, tourism can promote cultural heritage, strengthen local identity, and encourage intercultural exchange. Yet, it simultaneously risks cultural commodification, erosion of traditional values, and potential social conflict between locals and visitors. Environmentally, tourism raises public awareness about conservation and supports environmental protection efforts through eco-tourism initiatives. Despite this, unregulated tourism can cause serious environmental degradation, biodiversity loss, and overtourism, especially in fragile ecosystems. The findings emphasize the urgent need for sustainable tourism governance that balances economic benefits with social equity and environmental stewardship. Strategic planning, community involvement, policy enforcement, and responsible visitor management are essential to ensure that tourism remains a force for positive transformation rather than a driver of irreversible harm. This review underscores that without sustainability at its core, tourism’s benefits may be short-lived and come at high social and ecological costs.